THE EFFECTIVENESS OF USING SELF-CHECK IN ESSAY WRITING: STUDENTS PERCEPTIONS - Khairul Azmi; Zulhiddah Zulhiddah (UIN Sumatera Utara, 2026)
This study investigates students' perceptions of the effectiveness of self-check as a writing strategy in academic essay courses at the University in North Sumatra. Using a qualitative descriptive design, data was collected from 33 undergraduate students through class observation, analysis of essay draft documents, and structured questionnaires. The findings showed that the majority of students (81.8%) found self-check beneficial for improving structural organization, grammatical accuracy, and writing clarity. Nevertheless, neutral responses were prevalent regarding understanding checklist criteria (66.7%), and some students (24.2%) continued to have difficulty revising their essays after the self-examination process, underscoring the need for explicit instructor scaffolding and modeling. Perceptions of time efficiency vary widely, suggesting that self-check can initially impose cognitive demands on novice learners. Overall, the results show that self-examination not only improves technical writing competence but also fosters learners' metacognitive awareness and autonomy. These findings highlight the important role of structured tutoring, peer demonstration, and step-by-step instructional practice in maximizing the pedagogical benefits of self-check in writing teaching.